Self-reported occupational exposure and its association with sperm DNA fragmentation in infertile men: Occupation and sperm DNA fragmentation - Caliskan , Zeynep; Kucukgergin, Canan; Aktan, Gulsan; Bulut, Nurgul; Ozdemirler, Gul (Journal of Surgery and Medicine, 2023)
Background/Aim: Sperm quality has experienced a decline in recent years, with this issue being particularly pronounced in industrialized nations, suggesting a potential link to occupational exposures. Evaluating sperm DNA fragmentation can yield valuable insights into male fertility, although its association with occupational exposures remains less well-established. Our study aimed to investigate the relationship between self-reported occupational exposures and sperm DNA fragmentation in infertile men. Methods: This retrospective cohort study involved 391 infertile men who sought fertility treatment at a university clinic between 2017 and 2020. A brief questionnaire was administered to collect data on patients’ demographic characteristics, medical history, occupation, and exposure types. In this comparative study, patients were categorized into two groups based on their occupational exposures (the unexposed and exposed groups). The exposed group was further sub-grouped according to their specific exposure types, which included cement, solvents, metals, pesticides, mechanical vibration, and heat. The primary outcome in this study was assessed using the terminal deoxynucleotidyl transferase-mediated nick end-labeling test (TUNEL), with results expressed as the sperm DNA fragmentation index (DFI). Results: Patients in the exposed group exhibited a significantly higher sperm DFI compared to those in the unexposed group (14 [17] vs. 8 [9], P<0.001). After accounting for potential confounding factors, our results demonstrated that several occupational exposure factors significantly increased the risk of elevated sperm DFI (>15%) levels, including solvents (odds ratio (OR) 8.2, 95% confidence interval (CI) 3.6–18.5, P<0.001), metals (OR: 2.2, 95% CI: 1.0–4.7, P=0.048), pesticides (OR: 14.6, 95% CI: 1.6–130.7, P=0.016), mechanical vibration (OR: 2.6, 95% CI: 1.5–4.6, P<0.001), and heat (OR: 6.4, 95% CI: 1.7–23.5, P=0.005). Conclusion: The findings of our study corroborate earlier research suggesting that occupational exposures may have adverse effects on sperm DNA fragmentation in men. The identification and management of such exposures as part of routine clinical practice could offer a complementary approach to enhancing infertility treatment outcomes.